"It is me" – the replacement of the nominative by the oblique form in Danish subject complements. Issue 1 (2nd January 2018) - Jensen, Eva Skafte
Abstract: In this paper, it is suggested that the replacement of the nominative by the oblique form in Danish subject complements happened as a part of major structural changes taking place in Middle Danish. The major structural changes in question involve the shift from a case-rich to a case-poor language in Early Middle Danish/Late Middle Danish, and the changing of the status of the subject of the sentence in Late Middle Danish/Early Modern Danish. As one outcome, the distribution of the case forms of personal pronouns changed from being primarily following the traditional syntactic-semantic principle of conveying semantic roles and syntactic functions to following principles pertaining to information structure with notions like theme and rheme, prominence and focus/anti-focus. The approach is functional-structural.